The use of qr-code media in PKN subjects to foster the democratic character of 21st century students - Ade aransyah; Herpratiwi Herpratiwi; M. Mona Adha (ARKA INSTITUTE, 2022)
Character is a crucial thing that every human being must have. Along with the development of the times, students who today are commonly referred to as the millennial generation, must also have a strong character, so that they are not uprooted from the noble cultural roots of the Indonesian nation. 21st century education is no longer a discourse or idea, but must be able to be realized through a learning QR code is a two-dimensional image that presents a data, especially data in the form of text. The purpose of this study is to find out how to use QR-Codes in the field of education by utilizing QR-Codes as a learning medium, especially in Civics subjects with the hope that students can grow democratic character in various lives. The method used in this study used the SLR (Systematic Literature Review) method, data collection was carried out using documentation and reviewing all articles related to qr-code and civics subjects of democratic character. The result of this study is that the use of Qr-Code media can help the process of delivering messages or learning to students, so that they can achieve the expected learning outcomes, especially in PPKn learning in fostering democratic character, in 21st century students.